Comparação entre metodologias de extração de HPAs em água utilizando um planejamento fatorial com quantificação no CG/EM - Moura, Dayanne Chianca de (2009)
PAHs (Polycyclic Aromatic Hydrocarbons) are a group of organic substances which receive considerable attention because of the carcinogenic and mutagenic properties of some of them. It is therefore important to determine the PAHs in different environmental matrices. Several studies have shown the use of gas chromatography coupled to mass spectrometry as a technique for quantification of PAHs by presenting excellent detection limits. This study aimed to develop an analytical methodology for the determination of 16 PAHs listed by the USEPA, test two methods for extraction of PAHs in water from a 23 factorial design, quantify them through the analytical technique coupled to gas chromatography mass spectrometry (GC/MS) using the method developed, and finally apply the results in chemometrics. The sample was synthesized and subjected to tests of the 23 factorial design, which has the factors: the type of extraction technique (ultrasound and digester), the ratio solvent / sample (1:1 and 1:3) and the type of solvent (dichloromethane / hexane and acetone / dichloromethane). The responses of eight combinations of the factorial design were obtained from the quantification by external calibration in GC/MS. The quantification method was developed from an optimized adaptation of the USEPA Method 8270. We used the full scan mode as a way of acquiring the mass spectra of 16 PAHs. The time in which the samples were subjected to ultrasound was fixed at 10 min and held an investigation to establish the conditions of power and time in the digester. We had the best response in the investigation of the digester power of 100 watts and the time of six minutes. The factorial design of liquid-liquid extraction showed that the most representative factors were: the use of the digester as extraction technique, the ratio solvent / sample 1:1 and the use of a 1:1 mixture of dichloromethane / hexane as a solvent more suitable. These results showed that the 1:1 mixture of dichloromethane / hexane is an excellent mixture to recover the extraction of PAHs an aqueous sample using the microwave digester. The optimization of the method of separation, identification and quantification of PAHs in the GC/MS was valid for 16 PAHs present in each chromatogram of the samples